Advanced practice nurse capabilities: A mixed methods systematic review. Issue 1 (8th December 2022) - Hako, Laura; Turunen, Hannele; Jokiniemi, Krista
Abstract: Background: Global health challenges demand the optimal use of nurses' professional competence and capability. Competencies related to the roles of advanced practice nurses have been developed, but research on these nurses' capabilities remains limited. Aim: To summarise and compare the literature on the capabilities of advanced practice nurses and the dimensions of these capabilities. Methods: We carried out a mixed methods systematic review, using CINAHL, PubMed, and Scopus to search literature published between 1998 and 2021. The quality of the selected articles was evaluated with the JBI Critical Appraisal Tools. We employed abductive content analysis, including deductive and inductive analysis. The reporting was guided by the standards of the Preferred Reporting Items for Systematic Review and Meta‐Analysis Statement. Results: Eleven articles out of 357 met the inclusion criteria. We identified all five dimensions of Hase and Davis's (1999) capability framework: can apply competencies in familiar as well as unfamiliar situations, is creative, has a high degree of self‐efficacy, knows how to learn, and works well in teams. Additionally, we found a new dimension of capability: identifies factors affecting the scope of practice. Limitations: This mixed methods systematic review was conducted about a little‐studied topic. Because country‐specific differences exist and consensus on advanced practice nursing roles is lacking, the concept of advanced practice nurse capabilities cannot be directly generalised. Conclusions: Capability is a requirement and a necessity in the performance of advanced practice nurses. Identifying and defining the dimensions of advanced practice nurses' capabilities will lead the way in developing the roles, education, and capability assessments of advanced practice nurses. Identification of advanced practice nurses' capability will facilitate role understanding, visibility, and implementation in health care services. This can improve the quality and accessibility of care and improve the cost‐effectiveness of the use of health care professionals.